MANFAAT REBUSAN DAUN ALPUKAT UNTUK PENDERITA HIPERTENSI - Niftaqul Khasanah (STIKes Ibnu Sina Ajibarang, 2023)
Background: One of the ways avocado leaves work is to secrete a number of fluids and electrolytes as well as toxic substances. If the amount of water and salt in the body is reduced, the blood vessels will loosen so that blood pressure slowly decreases. The effect of the flavonoids contained in avocado leaves is efficacious as a diuretic. Diuretics play a role in treating diseases that cause fluid buildup in the body. This is related to the cure of certain diseases, especially those related to lowering blood pressure through the removal of water in the blood in hypertension and the disposal of certain substances in kidney disease (kidney stones), high uric acid, hypercalcemia, and diabetes insipidus (Paramawati, 2016).